Storytelling Method as a Media for Forming Character in Early Children in Timbong Village, Banggai Tengah District, Banggai Laut District, Central Sulawesi Province - Karmila P. Lamadang; Suma K. Saleh; Ayu Rosanti Tahawali; Putriyaningsi; Parida Maasing; Siti Suni (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
This service was carried out in Timbong village, specifically Timbong Kindergarten, with approximately 30 students divided into two classes, namely class A and class B. The process of storytelling or reading this book is carried out before the learning process begins and also when learning has been completed. The teacher reads in front of the class, and then the students listen. After reading fairy tales or stories, the teacher will give students the opportunity to ask questions. And at that time, the teacher will instill character by conveying the character values contained in the story